Minor Planet Center: data processing challenges. Issue Volume 10:Issue S318(2015) (1st March 2016) - Rudenko, Michael
Abstract: The Minor Planet Center receives up to several million astrometric observations of minor planets and comets each month. Given the volume of observations, the sheer number of known objects against which to possibly match, the shortness of the time interval over which each object was likely observed, and the uncertainties in the positions, and occasionally possible errors in times, reported, a number of data processing challenges present themselves. These include: Identifying observations of objects reported as new with already known objects; linking together sets of observations from different nights which may belong to the same object; determining if a set of observations has been assigned to the wrong object; determining if an object with a very short arc is possibly a Near-Earth object; prioritizing newly discovered objects in order of need of follow up; and, efficiently matching one or more observations with known objects.